Dari Herbal ke Hijau: Praktik Akuntansi Keberlanjutan di PT Sido Muncul Tbk dalam Era Green Economy - Ziyadatul Khoiroh; Ida Bagus Ketut Bayangkara (Pusat Riset dan Inovasi Nasional, 2025)
This article examines the sustainability accounting practices implemented by PT Industri Jamu dan Farmasi Sido Muncul Tbk in supporting the transition to a green economy through a literature study approach. This study relies on literature analysis of the company's 2024 sustainability report documents and academic references related to the concept of a green economy and sustainability reporting. The main objective of this study is to explore how Sido Muncul integrates economic, social, and environmental aspects into its business practices in accordance with the Global Reporting Initiative (GRI) and IFRS Sustainability Disclosure Standards (S1 and S2). The results of the analysis show that Sido Muncul has succeeded in implementing a comprehensive sustainability strategy through energy efficiency, emission reduction, use of local raw materials, and community empowerment. This article concludes that literature studies are an effective method for evaluating a company's sustainability accountability and assessing its contribution to sustainable development goals (SDGs).